Community structure, population dynamics and diversity of fungi in a full-scale membrane bioreactor (MBR) for urban wastewater treatment. (15th November 2016) - Maza-Márquez, P.; Vilchez-Vargas, R.; Kerckhof, F.M.; Aranda, E.; González-López, J.; Rodelas, B.
Abstract: Community structure, population dynamics and diversity of fungi were monitored in a full-scale membrane bioreactor (MBR) operated throughout four experimental phases (Summer 2009, Autumn 2009, Summer 2010 and Winter, 2012) under different conditions, using the 18S-rRNA gene and the intergenic transcribed spacer (ITS2-region) as molecular markers, and a combination of temperature-gradient gel electrophoresis and 454-pyrosequencing. Both total and metabolically-active fungal populations were fingerprinted, by amplification of molecular markers from community DNA and retrotranscribed RNA, respectively. Fingerprinting and 454-pyrosequencing evidenced that the MBR sheltered a dynamic fungal community composed of a low number of species, in accordance with the knowledge of fungal diversity in freshwater environments, and displaying a medium-high level of functional organization with few numerically dominant phylotypes. Population shifts were experienced in strong correlation with the changes of environmental variables and operation parameters, with pH contributing the highest level of explanation. Phylotypes assigned to nine different fungal Phyla were detected, although the community was mainly composed of Ascomycota, Basidiomycota and Chytridiomycota/Blastocladiomycota . Prevailing fungal phylotypes were affiliated to Saccharomycetes and Chytridiomycetes/Blastocladiomycetes, which displayed antagonistic trends in their relative abundance throughout the experimental period. Fungi identified in the activated sludge were closely related to genera of relevance for the degradation of organic matter and trace-organic contaminants, as well as genera of dimorphic fungi potentially able to produce plant operational issues such as foaming or biofouling. Phylotypes closely related to genera of human and plant pathogenic fungi were also detected. Graphical abstract: Highlights: The MBR sheltered a dynamic fungal community composed of a low number of species. Ascomycota, Basidiomycota and Chytridiomycota/Blastocladiomycota were most abundant. Population shifts correlated strongly with changes of external abiotic variables. Phylotypes related to both human and plant pathogenic fungi were detected.